The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5847/wjem.j.1920-8642.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital system delay in patients with ST-segment elevation myocardial infarction in Singapore

Abstract: Prehospital system delay in our patients was suboptimal. This is the first attempt at characterizing prehospital system delay in Singapore and forms the basis for improving efficiency of STEMI care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…In others, FMC was the time the ECG was performed by the EMS [18, 19, 20]. Moreover, other studies used the time of the patient’s phone call to the EMS as FMC [21]. Using the time patients called the ambulance as FMC may be unreliable because that phone call would be the only way to assess the patient’s condition.…”
Section: Discussionmentioning
confidence: 99%
“…In others, FMC was the time the ECG was performed by the EMS [18, 19, 20]. Moreover, other studies used the time of the patient’s phone call to the EMS as FMC [21]. Using the time patients called the ambulance as FMC may be unreliable because that phone call would be the only way to assess the patient’s condition.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment time delay is caused by various delays between symptom onset and reperfusion therapy. [ 5 , 6 ] “Patient delay” is defined as the time from symptom onset to the patient's seeking medical attention, that is, the first medical contact. [ 5 , 6 ] “System delay” is the time interval between the first medical contact and reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 , 6 ] “Patient delay” is defined as the time from symptom onset to the patient's seeking medical attention, that is, the first medical contact. [ 5 , 6 ] “System delay” is the time interval between the first medical contact and reperfusion. [ 5 , 6 ] Finally, “total treatment delay” is defined as the sum of the patient delay and the system delay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And a study by Cho et al [26] reported that high Hb and NLR values were associated with signifi cant mortality in coronary artery diseases when evaluated together. Boles et al [27] reviewed the development of coronary artery ectasia and short term prognosis. In AMI patients developing coronary artery ectasia, NLR values were identified to be lower compared to AMI patients not developing ectasia and also inflammatory response between the patients with developing and not developing coronary artery ectasia were reported to be different but this was indicated to have no prognostic value.…”
Section: Discussionmentioning
confidence: 99%